Traumatic testicular injuries in appalachia: A ten-year review from a level 1 trauma center and comparison to the national trauma data bank® - Mitchell, Katharina; Morley, Chad; Barnard, John (Frontiers in Urology, 2023)
While only 20% of the nation’s population lives in rural areas, 40% of the Appalachian population resides in rural areas. Due to the rural nature of this region we hypothesized this may have implications regarding the outcomes of traumatic testicular injuries (TTI), such as increased rate of organ loss. Here in, we report the findings of our 10-year retrospective study analyzing patients presenting with TTI to our rural tertiary care facility in comparison to an 8-year review of 8,030 TTI from the NTDB®. Of the 34,000 trauma patients reviewed, 23 (0.07%) had TTI which concurs with the NTDB® value of 0.2%. Blunt trauma accounted for 91.3% of TTI contrasting with NTDB® data suggesting 50.5% attributable to penetrating mechanisms. Firearm related injuries comprised 4.3% of TTI, but 38.3% of NTDB®’s. Motor vehicle collision/ motor cycle crash (MVC/MCC) accounted for 26.0%, similarly NTDB® data showed 26.6%. Median length of stay (LOS) was 1 day, and 3 for NTDB®. Scrotal exploration occurred in 90.4% of cases with 52.4% requiring orchiectomy, whereas NTDB® data suggested 48.3% and 23.4% respectively. In conclusion, compared to the NTDB® TTI data, Appalachia has a higher incidence of blunt mechanism, scrotal exploration rate, and testicular loss.